Antilymphocyte globulin for matched sibling donor transplantation in patients with myelofibrosis - Robin, Marie (Haematologica, 2019)
The use of antihuman T-lymphocyte immunoglobulin in the setting of transplantation from an HLA-matched related donor is still much debated. Acute and chronic graft-versus-host disease are the main causes of morbidity and mortality after allogeneic hematopoietic stem cell transplantation in patients with myelofibrosis. The aim of this study was to evaluate the effect of antihuman T-lymphocyte immunoglobulin in a large cohort of patients with myelofibrosis (n=287). The cumulative incidences of grade II-IV acute graft-versus-host disease among patients who were or were not given antihuman T-lymphocyte immunoglobulin were 26% and 41%, respectively. The corresponding incidences of chronic graft-versus-host disease were 52% and 55%, respectively. Non-adjusted overall survival, disease-free survival and non-relapse mortality rates were 55% versus 53%, 49% versus 45%, and 32% versus 31%, respectively, among the patients who were or were not given antihuman T-lymphocyte immunoglobulin. An adjusted model confirmed that the risk of acute graft-versus-host disease was lower following antihuman T-lymphocyte immunoglobulin (hazard ratio, 0.54; P=0.010) while it did not decrease the risk of chronic graft-versus-host disease. The hazard ratios for overall survival and non-relapse mortality were 0.66 and 0.64, with P-values of 0.05 and 0.09, respectively. Antihuman T-lymphocyte immunoglobulin did not influence disease-free survival, graft-versus-host disease, relapse-free survival or relapse risk. In conclusion, in the setting of matched related transplantation in myelofibrosis patients, this study demonstrates that antihuman T-lymphocyte immunoglobulin decreases the risk of acute graft-versus-host disease without increasing the risk of relapse.